Clinical contraindications to allergen immunotherapy: an EAACI position paper. Issue 8 (18th May 2015) - Pitsios, C.; Demoly, P.; Bilò, M. B.; Gerth van Wijk, R.; Pfaar, O.; Sturm, G. J.; Rodriguez del Rio, P.; Tsoumani, M.; Gawlik, R.; Paraskevopoulos, G.; Ruëff, F.; Valovirta, E.; et al.
Abstract Clinical indications for allergen immunotherapy (AIT) in respiratory and Hymenoptera venom allergy are well established; however, clinical contraindications to AIT are not always well documented. There are some discrepancies when classifying clinical contraindications for different forms of AIT as 'absolute' or 'relative'. EAACI Task Force on 'Contraindications to AIT' was created to evaluate and review current literature on clinical contraindications, and to update recommendations for both sublingual and subcutaneous AIT for respiratory and venom immunotherapy. An extensive review of the literature was performed on the use of AIT in asthma, autoimmune disorders, malignant neoplasias, cardiovascular diseases, acquired immunodeficiencies and other chronic diseases (including mental disorders), in patients treated with β‐blockers, ACE inhibitors or monoamine oxidase inhibitors, in children under 5 years of age, during pregnancy and in patients with poor compliance. Each topic was addressed by the following three questions: (1) Are there any negative effects of AIT on this concomitant condition/disease? (2) Are more frequent or more severe AIT‐related side‐effects expected? and (3) Is AIT expected to be less efficacious? The evidence, for the evaluation of these clinical conditions as contraindications, was limited, and most of the conclusions were based on case reports. Based on an extended literature research, recommendations for each medical condition assessed are provided. The final decision on the administration of AIT should be based on individual evaluation of any medical condition and a risk/benefit assessment for each patient.